2020
DOI: 10.1140/epjst/e2019-900094-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase-coherent caloritronics with ordinary and topological Josephson junctions

Abstract: We provide a brief and comprehensive overview over recent developments in the field of phasecoherent caloritronics in ordinary and topological Josephson junctions. We start from the simple case of a short, one-dimensional superconductor-normal metal-superconductor (S-N-S) Josephson junction and derive the phase-dependent thermal conductance within the Bogoliubov-de Gennes formalism. Then, we review the key experimental breakthroughs that have triggered the recent growing interest into phasecoherent heat transp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 126 publications
(148 reference statements)
0
15
0
Order By: Relevance
“…Thus, we also prove the operation of the T-SQUIPT as a phase-tunable thermal memory [9,10], where the information is encoded in the temperature of the metallic mesoscopic island. Besides their relevance in quantum physics, our results are pivotal for the design of innovative coherent caloritronics devices [11,12] such as heat valves [13] and temperature amplifiers [14] suitable for thermal logic architectures [15].…”
mentioning
confidence: 91%
“…Thus, we also prove the operation of the T-SQUIPT as a phase-tunable thermal memory [9,10], where the information is encoded in the temperature of the metallic mesoscopic island. Besides their relevance in quantum physics, our results are pivotal for the design of innovative coherent caloritronics devices [11,12] such as heat valves [13] and temperature amplifiers [14] suitable for thermal logic architectures [15].…”
mentioning
confidence: 91%
“…Recently, several works demonstrated that a quite wellknown device, a Josephson junction (JJ), can still deserve surprises when subject to a thermal gradient, i.e., unbalancing the temperatures at the two sides of the device. Thermal transport at the nanoscale and the research field of superconducting phase coherent caloritronics are attracting interest [1][2][3][4][5][6][7][8][9][10] due to the importance for the whole field of quantum technologies and quantum computing to master heat management at ultra-low temperatures. In this context, it was recently demonstrated that the Josephson transport [11][12][13] across a superconductor-insulator-superconductor (SIS) junction, formed by different superconductors residing at different temperatures, can show unexpected, and quite peculiar, features.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting hybrid systems, i.e., constituted of superconducting parts in electric contact with normal (non-superconducting) parts, are in practice coherent electron systems with striking thermodynamic equilibrium/transport properties, resulting in a wide variety of applicative devices: low-temperature sensitive thermometers [ 15 , 16 , 17 , 18 , 19 ], sensitive detectors [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], heat valves [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], caloritronics (heat computing) [ 11 , 37 , 44 , 45 , 46 , 47 , 48 ], solid-state micro-refrigerators [ 18 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], solid-state quantum machines [ 56 , 57 , 58 , 59 , 60 , 61 ], thermoelectric generators [ 62 ,…”
Section: Introductionmentioning
confidence: 99%